Whole-body low-dose computed tomography in primary patients with multiple myeloma - A. M. Danilina; L. P. Mendeleeva; I. E. Kostina; E. O. Gribanova; V. V. Ryzhko; Ya. B. Bal'zhanova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Imaging of bone lesions has an important role in diagnosis of multiple myeloma (MM) and evaluating the response to treatment. Computed tomography scan (CT) allows to detect osteolysis, plasmacytoma and the risk of fractures with high sensitivity. In the National Research Center For Hematologysince 2014 all patients with MM are diagnosed with the whole-body low-dose CT.The aim of the study was to demonstrate the sensitivity of the whole-body low-dose CT and to characterize localization, number and size of bone lesions in primary MM patients.Materials and methods. 50 patients with newly diagnosed MM were enrolled in the study. The diagnosis was established in accordance with international diagnostic criteria. All patients received the whole-body low-dose CT. According to the Durie-Salmon and ISS staging systems 62% and 66% of patients had stage III, respectively.Results. 96% of MM patients had bone lesions. In 30% of patients, bone involvement was the only criterion for CRAB. Pelvic bone lesions was most often diagnosed (92%). The destruction of the long bones of the arms and legs were most rarely detected (42% of patients) and mostly small. The presence of intraosseous plasmocytoma was noted in 40% of cases.Conclusion. The whole-body low dose CT was found to be the most sensitive modality for detection osteolytic bone lesions. Low-dose CT is available in MM case with bone disease only, for establish symptomatic stage. This patients require immedate antimyeloma treatment.